The role of track-based transportation by the development of eastern agglomeration of Budapest - Erdei, Attila (Studia Mundi – Economica, 2019)
The main function of public transport systems is mobility. This will ensure competitiveness, a fair quality of life and cohesion for society. The main actors in the transport system are passengers, service providers and decision-making bodies (e.g. the state, municipalities, public authorities). The eastern segment of Budapest's agglomeration is, and continues to be, densely networked by railway and suburban railway tracks. Studying the traffic map of the Budapest agglomeration, a loop, formed by the Gödöllő HÉV line and the MÁV 80a railway line (Budapest-Hatvan), is visible. Reviewing the history of local railways, we can discover evidence of the existence of additional lines that once had a significant impact on the economic and social development of the region. In my research, I study the effects of track-based transportation modes by the development of this part of the Budapest agglomeration.